Quality Changes during Storage of Smoked ’Cubes’ and ’Fillet Steaks’ Prepared from Marine Perch Lethrinus lentjan (Lacepede) - S., Sindhu; S., Krishnakumar; D.D., Nambudiri; Korath, Alphi (Fishery Technology, 2025)
The study evaluated keeping quality and storage life of cubes and fillet steaks from a marine perch King Emperor (Lethrintts lentjan, (Lacepede). Smoked cubes and fillet steaks were prepared using a brine concentration of 10% and brining time of 15 min, draining at +100C for 30 min, pre-drying in mechanical drier for 30 min at 500C and smoking at 800C for a period of 3 h. Smoked cubes and fillet steaks prepared using a standardised procedure were subjected to storage studies for a period of four months under different packings viz., (i) packed in PE bags (C) (ii) dried at 500C for Ih and packed in PE bags (SI) and (iii) dried at 500C for 1 h and packed in paper bags (S2). Quality changes during the storage period were monitored every 15 days time intervals for parameters viz., moisture content, per cent free fatty acids, thio barbituric acid value, total plate count, total fungal count and sensory quality. Samples packed in paper bags remained acceptable only upto 60 days of storage while samples packed in PE bags were acceptable upto 90 days.